Peningkatan Pengetahuan tentang Nutrisi yang Tepat pada Anak Usia Prasekolah - Suci Sulistyorini (LPPM Akbid Harapan Ibu Pekalongan, 2023)
Nutrition is one of the main determining factors in the quality of Human Resources. Providing poor nutrition, especially to children, will reduce the potential of community development resources. The low nutritional status of children will have a negative impact on improving the quality of human resources. Nutritional status can affect the physical condition and ability of students to follow the learning process, factors that can affect learning achievement, including biological factors, psychological and environmental conditions of students. The purpose of this activity is to increase the knowledge of the community, especially parents, about the importance of providing proper nutrition to preschool-aged children at Darma WanitaPersatuan Kindergarten, Dabuk Rejo , Lempuing OKI. The method in this community service is in the form of zoom (online) which was attended by 69 participants. The result of this activity was an increase in parental knowledge in providing proper nutrition to preschool-age children which can be seen from the post-test results. The conclusion from this activity is that there is an increase in parents' knowledge about the importance of providing proper nutrition according to the needs of preschool-aged children to support good health conditions and success in the learning process and learning achievement.